Factorization of Conditional Expectations on Kac Algebras and Quantum Double Coset Hypergroups - Chapovsky, Yu.; Kalyuzhnyi, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We prove that a conditional expectation on a Kac algebra, under certain conditions, decomposes into a composition of two conditional expectations of a special type and gives rise to a compact quantum hypergroup connected to a quantum Gelfand pair.